Particle Image Classification in Digital Holographic Microscopy by Normalized Cross Correlation - Tamrin, K. F.; Rahmatullah, B.; Samuri, S. M.; Mahamud, S. T. (2016)
Digital holographic microscopy is a promising technique for micro-scale fluid and solid measurements. It offers numerical advantage for digital image post-processing through manipulation of amplitude and phase embedded in the digital hologram. Previously, an off-axis digital holographic microscope was utilized to investigate aggregation of artificial platelets in the blood vessel. To mimic blood flow parameters to the minutest details, a cylindrical micro-channel was employed but this introduced astigmatism in the reconstructed particle images. This paper proposes the application of normalized cross correlation in feature matching technique so that astigmatic image can be efficiently classified prior to digital aberration correction. Here, automatic image classification relies on the computed normalized cross correlation coefficients with two dissimilar (astigmatic and focused) reference images. The method successfully classified eight images as astigmatic out of three hundred randomly chosen images. Limitation of the present method is also discussed. The method is foreseen useful for automatic image classification of a considerably large number of images usually acquired in digital holographic microscopy.